Urethral trichomoniasis in Iraqi females - Al-Kaisi, Aroub Abdul Rahman; Al-Janabi, Bahjat; Al-Tikriti, Raja (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Trichomonas vaginalis has long been recognized as a cause of infectious vaginitis in women different studies have demonstrated a significant burden of the parasite to cause urethritis as well. It has been assumed that the localization of parasite in the urethra may be responsible for the recurrence of vaginal infection.Aim: To evaluate the infection rate of urethral trichomoniasis and to evaluate two different laboratory’ methods used in the diagnosis.Methods: The present study consisted of420female patients presented with vaginal discharge with or without itching or disorient, investigated for urethral trichomoniasis who were compared to 50 females represented the control group.Each female M’as asked to collect first 10-20 ml of urine in a sterile screw capped bottle; the deposits were examined microscopically by:. Wet mount method for Trichomonas vaginalis.2. Culture in a specific ready made culture media.At the same time high vaginal swabs were taken and examined by both wet mount and culture methods for vaginal trichomoniasis.Results: Among 420 female patients examined for both urine sediments and vaginal swabs ,80 (19.04%) females were found to be positive for T. vaginalis by vaginal SM'abs. The parasite was seen either in the vagina alone in 39 (9.28%) or in the vagina and urethra in 41(9.76%), but it M’as never isolated from urethra alone.Conclusion: Trichomonas vaginalis is a common parasite offemale urethm as well as of the vagina, the localization of this flagellate in the urethra may be responsible for the recurrence of vaginal infection, since it may survive in the urethra, possibly in the Paraurethral glands (skene's) so when the treatment is limited to the vagina, this will often fail to reach the urethra and the trichomonads may contaminate the vagina following urination or sexual intercourse, that is why systemic rather than local treatment is indicated.